Prevalence of Barrett’s esophagus in obese patients undergoing pre-bariatric surgery evaluation: a systematic review and meta-analysis - Qumseya, Bashar; Gendy, Sherif; Wallace, Alexander; Yang, Dennis; Estores, Davis; Ayzengart, Alexander; Draganov, Peter V. (Endoscopy, 2020)
Introduction Obesity is a known risk factor for gastroesophageal reflux disease (GERD), Barrett’s esophagus (BE), and esophageal adenocarcinoma (EAC). Obese patients routinely undergo preoperative esophagogastroduodenoscopy (EGD) before bariatric procedures. We aimed to assess the prevalence of BE in this patient population.Methods We conducted a comprehensive literature search ending in March 2019. Search results were imported into covidence.org and screened by two independent reviewers. Heterogeneity was assessed using I2 and Q statistics and publication bias using funnel plots and the Orwin fail-safe test. Random-effects modeling was used in all analyses.Results Of 4087 citations, 77 were reviewed in full text and 29 were included in the final analysis based on our predetermined inclusion/exclusion criteria. A total of 13 434 patients underwent pre-bariatric surgery EGD. The pooled prevalence of BE using random-effects modeling was 0.9 % (95 % confidence interval [CI] 0.7 % – 1.3 %); P < 0.001; I2 = 58 %, Q = 67). In meta-regression analyses, controlling for sex and GERD, we found a positive association between mean body mass index (BMI) and the prevalence of BE (β = 0.15 [95 %CI 0.02 – 0.28]; P = 0.03). A linear relationship between the prevalence of BE and the prevalence of GERD was also noted (β = 3.9 [95 %CI 0.4 – 7.5]; P = 0.03).Conclusions Obesity has been postulated as a major risk factor for BE, yet we found that the prevalence of BE in morbidly obese patients undergoing preoperative EGD was very low. Therefore, obesity alone may not be a major risk factor for BE.